A flórula fanerogâmica das restingas do Estado do Pará. Família Moraceae Lindl - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2003)
The phanerogamous flora of the Restingas of Pará is constituted by 6 vegetal formations and about 300 species, among the families present, Moraceae Lindl. stands out, which is the object of this study. The specimens collected were identified by comparison with others deposited in the herbariums MG and IAN and through the existing literature, where it was verified the presence of 2 genera and 4 species, presented as follows: Brosimum guianense (Aubl.) Huber: tree 1 ° to 25 m tall, alternate leaves, elliptic, cartaceous to subcoriaceous; limb 1.5 to 8.2 in length and 1.0 to 3.2 in width, petiole 0.1 to 0.5 in length, acuminate apex, acute to obtuse base, entire margin. Inflorescence usually bisexual, discoid or broadly turbinate or hemispherical. It is found in the Restinga Forest. Ficus catappifolia Kunth & Bouché: tree 23,7 to 25,7 in tall, simple leaves, alternate, subobovate to oblong, leathery; limb 11,7 to 18 in long and 5,5 to 8 in wide, petiole 0,5 to 1,5 in long, obtuse to rounded apex, obtuse base. Cymose syconium-like inflorescence in leaf axils. It is found in the Moitas of the Open Shrub Formation and on dunes. Picus obtusifolia H. B. K.: tree 20 to 30 in height, broad crown, simple alternate leaves, subobovate to obovate, leathery; limb 9.8 to 24.7 in length and 5.7 to 11 in width, petiole 1.0 to 3.7 in length, obtuse apex, obtuse base. Cymose syconium-like inflorescence in leaf axils. It is located in the bushes of the Open Shrub Formation. Ficus guianensis Desv. ex Ham.: tree 26 in height, alternate leaves, oblong-lanceolate to elliptic, coriaceous; limb 9.3 to 13.4 in length and 4.3 to 5.9 in width, petiole 0.9 to 1.4 in length, acute to obtuse apex, acute to obtuse base. Cymose syconium-like inflorescence in leaf axils. It is found in the Moitas of the Open Shrub Formation and Restinga Forest.
The Phanerogamic Flora of the Restingas of the State of Pará. Family Moraceae Lindl
Keywords: Moraceae lindl.; Restinga; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::MORFOLOGIA VEGETAL